A philosophical investigation of virginity testing in Kwazulu-Natal: a contribution to the multiculturalism and feminism debate. - Dlamini, Lennox Khulekani (Stellenbosch : Stellenbosch University, 2021)
Thesis (MPhil)--Stellenbosch University, 2021.